Synthetic Studies towards the Total Synthesis of Indole Alkaloids Containing Indolyl Lactam Frameworks - Tan, Dong-Xing; Han, Fu-She (Synlett, 2020)
In this account, recent progress on the synthetic studies of several monoterpene indole alkaloids, (±)-mersicarpine, misassigned (±)-tronoharine, and (±)-leuconodines D and E, is summarized. Specifically, the rationale for the design and development of the Lewis acid catalyzed SN1-type substitution and formal [3+3] cycloaddition reaction of indol-2-yl carbinols, and the Pd-catalyzed aerobic oxidative intramolecular Heck cross-coupling of indolyl amides tethered with a terminal olefin functionality, are emphasized. These key reactions set the basis for the rapid construction of the fused ring skeleton containing an all-carbon quaternary center at the indol-2-yl position.1 Introduction2 Synthetic Study of (±)-Mersicarpine3 Synthetic Study of the Misassigned (±)-Tronoharine4 Study of the Asymmetric Reaction of Indol-2-yl Carbinols5 Synthetic Study of (±)-Leuconodines D and E6 Conclusion
Keywords: synthesis; indole alkaloid; mersicarpine; tronoharine; leuconodine; indolyl carbinol; oxidative Heck coupling